The history of the development of SD Muhammadiyah Kauman Yogyakarta from 1980 to 2015 - Ye Lin Swe (Journal of Social Studies (JSS), 2016)
The purpose of the research is to reveal (1) the historical background of SD Muhammadiyah Kauman, (2) the development of SD Muhammadiyah Kauman from 1980 to 2015, and (3) the learning model which is applied at SD Muhammadiyah Kauman. This research used the historical research method focusing more on the development of the history SD Muhammadiyah Kauman Yogyakarta from 1980 to 2015. There were five steps in this study: choosing topics, heuristics, primary source, secondary sources and critical resources when collecting the data. The techniques of collecting data are interview, documentation, observation, books and literature study.  The result of this research shows that SD Muhammadiyah Kauman after the collaboration with SD Muhammadiyah Sapen makes good progress in administration of school, an increase of the number of students, and infrastructure of the school which gets better than before. The development of quality and quantity of students from year to year. The other result is the model of learning which is applied at SD Muhammadiyah Kauman is accordance with the needs of IPTEK, model of learning through playing, observation, and discussion between the teacher and the students, and to find ideas of student himself through reading books in the school library.Keywords: Education, the school of Muhammadiyah, curriculum